2016
DOI: 10.5812/ircmj.22940
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review of Adipose-derived Mesanchymal Cells from History to Approaches

Abstract: Context: After about 40 years from the discovery of bone marrow stem cells, the adipose stem cells (ASCs) were identify and the applications of these cells in different fields including the medical and biomedical fields have always attracted the attention of the scientists. The great quantity of stem cells obtained from adipose tissue allows the scientists to rapidly apply these primary cells without culture expansion. Evidence Acquisition: Human has different types of fat tissues and each has its own applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The cellular fibroblast pellet was extracted from a skin biopsy punched from a normal adult ear under sterile conditions at skin intervention clinics using a standard cell separation protocol. The sample was primarily cultured in high glucose DMEM with 10% FBS in a flask to achieve 70–80% confluence in each flask .…”
Section: Methodsmentioning
confidence: 99%
“…The cellular fibroblast pellet was extracted from a skin biopsy punched from a normal adult ear under sterile conditions at skin intervention clinics using a standard cell separation protocol. The sample was primarily cultured in high glucose DMEM with 10% FBS in a flask to achieve 70–80% confluence in each flask .…”
Section: Methodsmentioning
confidence: 99%
“…22−24 Furthermore, recent investigations have revealed that multipotent, plastic mesenchymal stem cells (MSCs), which benefit from paracrine signaling, are highly potent to be utilized as allogenic sources for enhancing wound healing. 25,26 Paracrine signaling contributes to the regenerative ability of MSCs either through the whole secretome or even through the exosomes; this signaling has been reported to be effective in wound healing and scar reduction through modulating the ratios of MMP-3/TIMP1, TGF-β3/TGF-β1, and (type III collagen)/ (type I collagen), which reduce the myofibroblast differentiation and eventually promote ECM reconstruction and wound healing. 27 As natural bioreactors, MSCs secrete lots of bioactive molecules, which could accelerate wound healing by increasing the migration of the dermal fibroblast and keratinocyte into the wound area, resulting in accelerated wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…The main concerns of cell therapy are limited replicative lifespan, risk of teratoma formation after transplantation, and ethical issues . Eukaryotic cells can be considered as robust natural bioreactors that produce a variety of bioactive molecules with the appropriate ratio, which can act as therapeutic agents in the wound-healing process and enhance the regeneration rate of the lost/damaged tissue. Furthermore, recent investigations have revealed that multipotent, plastic mesenchymal stem cells (MSCs), which benefit from paracrine signaling, are highly potent to be utilized as allogenic sources for enhancing wound healing. , Paracrine signaling contributes to the regenerative ability of MSCs either through the whole secretome or even through the exosomes; this signaling has been reported to be effective in wound healing and scar reduction through modulating the ratios of MMP-3/TIMP1, TGF-β3/TGF-β1, and (type III collagen)/(type I collagen), which reduce the myofibroblast differentiation and eventually promote ECM reconstruction and wound healing . As natural bioreactors, MSCs secrete lots of bioactive molecules, which could accelerate wound healing by increasing the migration of the dermal fibroblast and keratinocyte into the wound area, resulting in accelerated wound healing. , MSCs also increase the level of angiogenesis via increasing the levels of VEFG and HGF, increasing the microvessel density, and improving the microcirculation in the wound. , The immunomodulatory features of the MSCs can be harnessed to modulate the immune responses and inflammation .…”
Section: Introductionmentioning
confidence: 99%